A twisted chromophore powers a turn-on fluorescent protein chloride sensor - Cheng Chen; Vishaka Pathiranage; Whitney S. Y. Ong; Sheel C. Dodani; Alice R. Walker; Chong Fang (Proceedings of the National Academy of Sciences, 2025)
Fluorescent proteins (FPs) are noninvasive genetically encodable probes that have revolutionized bioimaging and health fields with vivid images and an ever-growing repertoire from jellyfish to sea anemones and corals. Inside the protein matrix, chromophore nonplanarity and flexibility have long been argued to govern the fluorescence efficiency of FPs, yet their fundamental roles and relative importance have been elusive which hinder the rational design of versatile FPs and biosensors. Herein, we tackle this central question by investigating two recently engineered FP-based turn-on chloride (Cl – ) sensors, ChlorON1 and 3, using an ultrafast electronic and vibrational spectroscopic toolset together with advanced multireference simulations for both structure and spectrum. We elucidate that fluorescence enhancement of the chloride-bound ChlorON3 stems from a substantially more twisted chromophore than ChlorON1 via comprehensive simulations starting from the available crystal structure of parent protein (mNeonGreen), also featuring an enhanced radiative pathway due to an adjacent leucine residue in the emissive population. This finding indicates that the commonly stated chromophore planarity is not, but conformational rigidity is, the decisive factor for high fluorescence efficiency. Such mechanistic insights into FPs are generalizable to chromoproteins and other photosensitive biomolecules, which can facilitate the targeted design of brighter and/or tunable biosensors.